Latitudinal patterns of travel among returned travelers with influenza: results from the GeoSentinel Surveillance Network, 1997-2007 - Boggild, Andrea; Wilder-Smith, Annelies (Journal of travel medicine, 2012)
AbstractBackground. Influenza is a common vaccine‐preventable disease among international travelers, but few data exist to guide use of reciprocal hemisphere o
Published: 08 December 2011
Gesehen am 05.10.2018